PENGARUH PENGENDALIAN JADWAL MATERIAL TERHADAP KINERJA PRAKTEK BENGKEL DAN LABORATORIUM JURUSAN TEKNIK SIPIL INSTANSI X DI MALANG - Sitti Safiatus Riskijah (Prokons: Jurnal Teknik Sipil, 2017)
In fiscal year 2014 the practice material needs about 36% of the DIPACivil Engineering Department budgetfundsfor the fiscal year2014.Thus, needs proper management, so that the procurementof materialsdone as needed and can be used effectivelyandefficiently. This study aimstodetermine the level ofcontrolthe materialthat has been applied, andthe schedule of material management influence towards the performancepracticein terms ofschedule materialpractice aspects.The research data in the form of primary data obtained by distributing questionnaires to direct executors as the material handler and the responsible party of practice activity at the Civil Engineering Department of X at Malang. Number of samples around 8 with 6 executive responsible party. Data were analyzed descriptively and then analyzed with regression method using SPSS 20.The results shows: 1) Executors implement control of schedule practice material to the workshop and laboratory reasonably well; and 2) Control of material arrivals schedule shows significant effect of the time of practice execution or completion. With the contribution of the effect of 72.2%.  Keywords: control, schedule, materials, practice, performance